Pemanfaatan YouTube Sebagai Media Pembelajaran Saat Pandemi COVID-19 untuk Mengembangkan Kreativitas Mahasiswa - Hikmawati Hikmawati; Syahrial Ayub (Unram Journal of Community Service, 2021)
The COVID-19 pandemic caused a change in the learning system from offline to online. Lecturers can use social media as a digital literacy-based learning media. The purpose of this community service activity is to develop student creativity through the use of YouTube as a learning medium during the COVID-19 pandemic. This activity was held online during 3 meetings with the number of participants as many as 23 students. The method of activity is: 1) on September 10, 2021 provides YouTube video links for the deepening of scientific approach material; 2) on September 17, 2021 designing learning activities with a scientific approach based on YouTube videos; 3) on September 24, 2021 made a learning video to explain the concept of high school physics with a scientific approach. Lecturers observe the creativity of students at every meeting. Indicators of creativity consist of fluent thinking skills, flexible thinking skills, original thinking skills, detail thinking skills, curiosity, and being challenged. Assessment of student creativity using scale 4. The increase in creativity score at the initial meeting and the final meeting is calculated using N-gain. The results showed the creativity score of students increased from 2.45 (poor criteria) at meeting 1 to 3.07 (good criteria) at meeting 2 and by 3.47 (good criteria) at meeting 3. The average creativity of students is 3.00 which is on good criteria. The lowest indicator is the skill of smooth thinking of 2.87 (poor criteria) while the highest indicator is to feel challenged by 3.17 (good criteria). The N-gain value of 66 is at the moderate criterion. Thus, the use of YouTube as a learning medium can develop student creativity, especially the attitude of feeling challenged